PREDICTION OF CARBON BEHAVIORS WITH EMPHASIS ON CLEAN DEVELOPMENT MECHANISM (CDM): THE DARAJAT GEOTHERMAL FIELD - PERMATASARI (NIM : 22611024), DEWI
The Clean Development Mechanism (CDM) is a flexibility mechanism of the Kyoto Protocol under the United Nations Framework Convention on Climate Change (UNFCCC). CDM assist the developing countries to trade their Certified Emission Reduction (CERs) to the developed countries. To date, Darajat Unit-III proposed a CDM program in 2007 and in April 2009 Darajat Unit-III received its first CER. This study presents the preliminary study of carbon behavior prediction, emphasized on CDM, by considering the reservoir behaviors as the source of emissions in geothermal field. The simulation was done using TOUGH2 EOS-2, a TOUGH2 Module considering a single well model completed with CO2 as an additional calculated variable. Three production wells in used Darajat, DRJ-08, DRJ-24, and DRJ-21, with a significant different volume of CO2 were selected to represent a total of 30 existing wells. The simulation results shows a constant value of CO2/steam ratio. Beside conducting a simulation to predict the carbon behaviors in the existing Darajat Unit-III, this preliminary study also calculated the total emissions from two different new scenarios. Both of the scenarios were assumed to be situated in a hypothetical location with two different additional capacity. The first scenario was to generate an additional 110 MW, in which resulted a total of 27,046 to 89,942 ton CO2-eq./year emission. The other scenario was to develop new geothermal project of 55 MW, in which resulted a total of 13,523 to 44,971 ton CO2-eq./year emission.